Heading for crisis [videorecording]. - Velez, Jose Mari. ([Quezon City] GMA Radio Television News and Public Affairs)
A scenario on the continuing economic difficulties attributed to floods, scarcity of transportation and unbearable roads, illegal housing and deterioration of health standards in the metropolis.
Host, Jose Mari Velez.
Keywords: Manila metropolitan area -- Economic conditions; Philippine economy